Poverty and Middle Level Achievement in a Common Core State: What are we Missing? - Lauren Davis (Middle Grades Review, 2021)
The purpose of this study was to determine whether a significant difference exists in academic achievement between all students and economically disadvantaged students when compared by socioeconomic levels in the North Carolina middle grades learner (as measured by reading and mathematics standardized tests). It also sought to determine whether significant differences exist between economically disadvantaged students in the various middle level grades (6-8). This article analyzes proficiency data in state-level standardized assessments from a most recent testing year (2017) with North Carolina middle level students. While student socioeconomic status and its impact on student achievement are the focus of this article, this study also analyzes proficiency trends while delving into inequity implications. A review of the literature establishes a long-term pattern of an achievement gap with disadvantaged students. Recognizing the impact of poverty on student achievement as measured by standardized tests, the author questions the explicit practices of the middle level educator to better support economically disadvantaged middle level students. This study illuminates some evidence-based best practices while also exploring the asset-based learning model and growth mindset as strategies to support adolescent learners experiencing high poverty.
Keywords: Poverty; Standardized Assessments; Common Core